Trade in services and human development: A first look at the links - Ben Shepherd; Gloria Pasadilla (Asian Development Bank Institute (ADBI), 2011)
Some services directly produce outputs that are important for human development, such as basic human services. Many other services are important inputs into the production and distribution of goods that are necessary for human development purposes. A more efficient services sector should mean that such goods and services can be made available to poor people more cost effectively and more broadly. In line with this reasoning, we find in the data that less restrictive services trade policies are associated with better human development outcomes across a range of sectors. Appropriate services trade liberalization can therefore promote human development directly through improved outcomes, in addition to indirectly effects through the income channel.
Keywords: F13; O15; O24; 330; Internationaler Dienstleistungsverkehr; Entwicklung; Außenhandelsliberalisierung; Wirkungsanalyse; Welt